Application of jaban watermelon exocarp powder in low‐calorie ice cream formulation and evaluation of its physicochemical, rheological, and sensory properties. Issue 9 (2nd August 2021) - Ghaedrahmati, Shiva; Shahidi, Fakhri; Roshanak, Sahar; Nassiri Mahallati, Marzieh
Abstract: Jaban watermelon seeds are one of the most favorable nuts in Iran. The production of these popular nuts leaves a large amount of environmental pollutants. The aim of this study was to evaluate the rheological, physicochemical, and sensorial properties of ice cream by replacement of milk cream with watermelon exocarp powder (WEP) at 0%, 20%, 40%, 60%, 80%, and 100% levels. The results showed that although all samples showed the pseudo‐plastic behavior rheologically, the replacement of cream with WEP significantly affected the physicochemical properties. Adding the WEP increased the textural properties and melting resistance of the samples, whereas overrun, draw temperature, and the flow behavior index decreased, significantly ( p  < 0.5). Hedonic evaluation showed not only that adding the WEP at 20% level does not have a significant effect on sensory properties, but also received the highest scores. Finally, regarding the high amount of fiber and minerals in WEP can lead to produce lower calorie ice cream with higher nutritional value. Novelty impact statement: A new look on using Jaban watermelon environmental pollutants to produce economically and nutritionally valuable by‐products. Investigation of macro‐ and micro compounds in watermelon exocarp powder. Producing of low calorie and high nutritional value ice cream by replacing cream with WEP.